Familial acquired thrombotic thrombocytopenic purpura in siblings – no immunogenetic link with associated human leucocyte antigens. (7th December 2016) - Gödel, Philipp; Fischer, Julia; Scheid, Christoph; Gathof, Birgit S.; Wolf, Jürgen; Rybniker, Jan
Abstract: Acquired immunoglobulin G (IgG)‐mediated thrombotic thrombocytopenic purpura (TTP) has not yet been described in non‐twin siblings. We report two cases of acquired TTP in Caucasian sisters with inactive ADAMTS13 metalloprotease due to ADAMTS13 autoantibodies suggesting a role of genetic determinants in this life‐threatening disease. However, human leucocyte antigen (HLA) class II types presumably associated with acquired TTP were not identified in the patients, indicating that HLA class II typing may not be useful in acquired TTP risk assessment of family members.